2018
DOI: 10.1093/mnras/sty1909
|View full text |Cite
|
Sign up to set email alerts
|

Vortex formation and survival in protoplanetary discs subject to vertical shear instability

Abstract: Several protoplanetary disks observed by ALMA show dust concentrations consistent with particle trapping in giant vortices. The formation and survival of vortices is of major importance for planet formation, because vortices act as particle traps and are therefore preferred locations of planetesimal formation. Recent studies showed that the vertical shear instability (VSI) is capable of generating turbulence and small vortices in protoplanetary disks that have the proper radial and vertical stratification and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
94
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 44 publications
23
94
1
Order By: Relevance
“…We assumed axisymmetry throughout. This simplification overestimates the strength of VSI turbulence (Manger & Klahr 2018). For example, Stoll & Kley (2016) found that passive particles with Tstop = 0.002 can settle to H d 0.66Hg; whereas we find such particles remain perfectly mixed with the gas.…”
Section: Caveats and Outlooksmentioning
confidence: 54%
“…We assumed axisymmetry throughout. This simplification overestimates the strength of VSI turbulence (Manger & Klahr 2018). For example, Stoll & Kley (2016) found that passive particles with Tstop = 0.002 can settle to H d 0.66Hg; whereas we find such particles remain perfectly mixed with the gas.…”
Section: Caveats and Outlooksmentioning
confidence: 54%
“…We note that the Reynolds stresses measured in all three of our magnetized models are noisy and are smaller than those obtained in 3D simulations (α ∼ 10 −3 ; e.g. N13; Manger & Klahr 2018) which allow for better averaging. We find the same holds for hydrodynamic simulations.…”
Section: Radial Transportmentioning
confidence: 63%
“…We find the same holds for hydrodynamic simulations. The higher Reynolds stress in 3D is likely due to the formation of vortices (Richard et al 2016;Manger & Klahr 2018), though the kinetic energy fluctuations remain very similar between 2D and 3D. Further study with non-ideal MHD in 3D is needed to better constrain the range of Reynolds stress.…”
Section: Radial Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The trap distance d quantifies typical radial separation of the trap and τ trap a trap's typical lifetime. We set d = 5h g and τ trap to 100 orbits, as found numerically by Dittrich et al (2013); Manger & Klahr (2018).…”
Section: Pebble Flux-regulated Planetesimal Formationmentioning
confidence: 99%